KOMPARATIF STUDI TENTANG PENGARUH MUSICSCAPE TERHADAP CUSTOMER SATISFACTION DI COFFEE SHOP KOTA PADANG - Wulansari, Nidia; Adrian, Arif; Wulandari, Dwi Pratiwi; Pratama, Vischa Mansyera; Putri, Athaya Fathinah (Ensiklopedia of Journal, 2024)
The purpose of this study is to analyze the effect of Musicscape on Customer Satisfaction at Coffee Shops in Padang City, and compare generation Y with generation Z. This type of research is classified as associative comparative research. In this study, the Endogenous variable (effect) is Customer Satisfaction (Y), the Exogenous variable (cause) is Musicscape (X), the population in this study is an unlimited population, which is consumers of coffee shops that provide music facilities in Padang city. The sample size for this study is 204 participants, with 102 samples of generation y and 102 samples of the centennial generation. This study used purposive sampling technique. The data analysis used is descriptive analysis using simple regression tests with the help of IBM SPSS version 29.00. The results showed that Musicscape has a positive and significant effect on customer satisfaction in Padang City Coffee Shop for both generations. This finding indicates that Musicscape innovation has succeeded in increasing customer satisfaction from Generation Y and Generation Z, providing a positive and significant effect on customer satisfaction.Keywords: Musicscape, Customer Satisfaction, Coffee Shop, Generation Y, Generation Z